Mythologies - Barthes, Roland 1915-1980 (Paris Éditions du Seuil, 1957)
Mythologies is a 1957 book by Roland Barthes. It is a collection of essays taken from Les Lettres nouvelles, examining the tendency of contemporary social value systems to create modern myths. Barthes also looks at the semiology of the process of myth creation, updating Ferdinand de Saussure's system of sign analysis by adding a second level where signs are elevated to the level of myth.
Keywords: Philosophy; Mythology; Semiotics; France